(untitled) (Research, Society and Development, 2022)
The objective of this study is to describe the bibliometric panorama of international scientific production on the search for respiratory symptoms in primary care. This is a bibliometric study, with a quantitative approach, carried out in May 2021 in the Web Of Science database. Data were extracted into Microsoft Software Excel® 2010 and organized in Microsoft Word 2010. The VOSviewer software (version 1.6.16.) was used to build and visualize bibliometric networks. 206 scientific articles related to the proposed theme were identified. The prevalent year of publication was 2020 with 29 (14.07%) publications, the country with the highest number of scientific productions was the United States with 82 (39.80%) publications, there was a predominance of English in 196 (95, 14%) publications, the journal that most published on the subject was the International Journal of Tuberculosis and Lung Diseas with 14 publications. The United States (USA) was the country with the highest number of scientific productions, linked to the fact that the US invests considerably in research and innovation, in addition to reinforcing that most studies on tuberculosis originate from high-income countries with low incidence of tuberculosis. tuberculosis. Thus, tuberculosis behaves as a global public health problem. Countries with a high incidence of the disease need to align the implementation of the pillars of the strategy towards the end of tuberculosis, with an emphasis on research and innovations so that the goals are achieved by 2035.